MEDIA SOSIAL DAN PENGARUHNYA TERHADAP HAFALAN AL-QUR'AN ANAK USIA PENDIDIKAN DASAR: SEBUAH TELAAH KRITIS - Ahmad Shofiyuddin Ichsan; Roizatul Faruk; Muhammad Al Faruq; Moch. Azis Qoharuddin (As-Sulthan Journal of Education, 2025)
Social media has become an integral part of the lives of elementary school-aged children in Indonesia, with the majority introduced to it before the age of 13. This phenomenon raises concerns about the focus on Quran memorization, the foundation of early Islamic education. Through library research, this study aims to analyze the dual influence of social media on the Quran memorization process in elementary school-aged children (7-12 years old). The approach used involved a literature review of journals, proceedings, and recent academic sources, using descriptive-interpretive content and thematic analysis methods. The results revealed positive impacts, such as increased motivation through YouTube content and access to engaging, interactive educational materials. However, negative impacts were more prevalent, including decreased attention span, disruption of Quran memorization routines due to entertainment notifications, and significant time wastage. The study's conclusions emphasize the need for strict digital literacy regulations, collaborative supervision by parents and teachers, and structured integration of social media into the elementary Islamic education curriculum. These steps are expected to maximize benefits while minimizing risks, while filling the gap in a holistic analysis encompassing the cognitive, affective, and habitus dimensions.